2017
DOI: 10.1111/hsc.12445
|View full text |Cite
|
Sign up to set email alerts
|

Bringing it all back home: Understanding the medical difficulties encountered by newly released prisoners in New Orleans, Louisiana - a qualitative study

Abstract: Formerly incarcerated persons (FIPs) face a disproportionate risk of death and serious illness in the immediate post-release period. Therefore, it is a critical time to initiate community-based care for chronic illnesses and behavioural disorders. Little is known about the unique transitional health and social support needs of FIPs in Louisiana, which has the highest incarceration rate in the world. As the average age of prisoners in the United States rises, the release of older prisoners with chronic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…While some research has found health benefits of incarceration, with improvements in mental and physical health while in prison because of improved access to services while incarcerated (Shaw, 2011), there is a dramatic decline in health following release from prison, making post-release prisoners a higher risk population than currently incarcerated offenders (Kinner et al, 2015). As a result of this decline in health, and the high mortality and suicide rates post-release from prison (Binswanger et al, 2012;Vail et al, 2017) it is essential that this transition period is made as smooth as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some research has found health benefits of incarceration, with improvements in mental and physical health while in prison because of improved access to services while incarcerated (Shaw, 2011), there is a dramatic decline in health following release from prison, making post-release prisoners a higher risk population than currently incarcerated offenders (Kinner et al, 2015). As a result of this decline in health, and the high mortality and suicide rates post-release from prison (Binswanger et al, 2012;Vail et al, 2017) it is essential that this transition period is made as smooth as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The transition period from prison to the community is a high risk time for offenders, with post-release prisoners reporting a lack of support and increased levels of stress resulting from the process of reintegrating into the community (Binswanger et al, 2012;Vail et al, 2017). Mortality rates during the first two weeks following release can be as much as 12.5 times higher than the general population (Binswanger et al, 2012), and suicide peak one month after release from prison (Pratt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous social, logistical, and financial barriers may preclude recently released individuals from accessing much-needed care. 19,20 In 2013, a university-based physician, an executive director of a nonprofit agency that organizes and advocates for FIPs, and a researcher with expertise in community-academic partnered research agreed to collaborate to improve health services for FIPs in New Orleans, Louisiana. All three shared the common experience of caring for incarcerated or formerly incarcerated individuals.…”
Section: Prisoner To Patientmentioning
confidence: 99%
“…Along with a medical student, the team conducted formative research on the needs of FIPs in Louisiana. 20 Based on findings, the As a separate, but related effort, the team began the Prisoner to Patient project in 2015 to develop a research agenda focused on the unique health needs of FIPs. The researcher and the executive director agreed to co-lead the P2P-supported project.…”
Section: Prisoner To Patientmentioning
confidence: 99%